2008
DOI: 10.1177/0891242408318738
|View full text |Cite
|
Sign up to set email alerts
|

Banking on the Margin in Canada

Abstract: This article analyzes the socioeconomic characteristics of the financially excluded in Canada using the 1999 Statistics Canada Survey of Financial Security and two surveys sponsored by the Financial Consumer Agency of Canada in 2001 and 2005. The authors find that financial exclusion is more concentrated among low-income Canadians; low-income, low-level of assets, and single-parent statuses are correlated with being unbanked. A review of banking preferences of low-income people indicates that economically disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 6 publications
5
32
0
Order By: Relevance
“…A more careful analysis of this relationship was previously undertaken with the 1999 SFS data. Using probit regression analysis of the 1999 SFS, Buckland and Dong (2008) investigated factors associated with financial exclusion and did consider household budget making. They found that "in terms of acquiring basic financial services, households that have a budget are not statistically different from those that do not" (Buckland & Dong, 2008, p. 258).…”
Section: Data On Financial Literacymentioning
confidence: 99%
“…A more careful analysis of this relationship was previously undertaken with the 1999 SFS data. Using probit regression analysis of the 1999 SFS, Buckland and Dong (2008) investigated factors associated with financial exclusion and did consider household budget making. They found that "in terms of acquiring basic financial services, households that have a budget are not statistically different from those that do not" (Buckland & Dong, 2008, p. 258).…”
Section: Data On Financial Literacymentioning
confidence: 99%
“…Financial exclusion hinders social development (Amaeshi, Ezeoha, Adi & Nwafor, 2007;Buckland & Dong, 2008;Fuller & Mellor, 2008;Gómez-Barroso & Marban-Flores, 2013;Horska et al, 2013;Hudon, 2008;Leyshon et al, 2004;Myers et al, 2012;Solo, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these types of programmes are mainly used by low-income, vulnerable, and formerly excluded populations. Therefore, it is not surprising that it is one of the most frequently used programmes in the UK, US, India, Indonesia, South Africa, Brazil, Uganda, and Canada (Buckland & Dong, 2008;Chibba, 2009;Cnaan et al, 2011;Duncombe, 2012;Ketkar et al, 2012;Marshall, 2004;McKillop et al, 2007;Mishra & Singh Bisht, 2013;Stapleton, 2013;Wentzelet al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 This sector is generally considered to include "payday lenders, cheque-cashers, rent-to-own shops, pawnshops, income-tax refund advancers and sub-prime lenders" (Buckland 2008 , 1) 13 For a wholesome discussion of the increase of fringe credit services in Canada and its impact on low income communities see Buckland and Dong 2008. Enhancing Community Investment in Canada Page 26 of segments of their population being economically excluded: British economic exclusion was a key motivator for the American Revolution, and the exclusion of black people from credit markets motivated community-based responses as early as 1693 (Immergluck 2004, 55). …”
Section: Overview Of the Community Investment Sector In The United Stmentioning
confidence: 99%